Pengaruh Pola Pemanfaatan Ruang Terbuka Hijau terhadap Dinamika Perubahan Kualitas Udara Akibat Pandemi Covid-19 - Siti Badriyah; Hermawan, Rachmad; Setiawan, Yudi; Wijayanto, Arif Kurnia; Prasetyo, Lilik Budi; Permatasari, Prita Ayu; Rushayati, Siti Badriyah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
The Covid-19 pandemic has had a global impact on all sectors including the environment. The spread of Covid-19 is very much influenced by human activity and mobility. Human activities are also closely related to air pollutant emissions. High concentrations of air pollutants during the Covid19 pandemic will increase the risk of being exposed to Covid-19. Jakarta and its surrounding area (known locally as Jabodetabek) have high population density. These cities are economic and industrial centers. Air pollutant emissions in these cities are very high. High concentrations of air pollutants during the Covid-19 pandemic will increase the risk of being exposed to Covid. To anticipate this problem, the government made a Large-Scale Social Restriction Policy (PSBB). Limited human activities, in addition to having an impact on reducing the risk of humans being exposed to Covid-19 from the droplets released by tested-positive of Covid-19, also have an impact on reducing emissions of air pollutants so that they can reduce the risk of being exposed to Covid-19. Several variables that influence vulnerability and risk to exposure to Covid-19 are the distribution of settlements, roads, economic centers (markets, business centers, industrial centers), and human mobility. In this study, we will also analyze the role of green open space on the risk of exposure to Covid-19. Green open space plays an important role in reducing air pollutants so that it will also affect the risk of being exposed to Covid-19. This study aimed to 1) examine the distribution of air pollutants based on the vulnerability and risk of COVID-19 in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek), and 2) examine the results of the overlay between land cover and vulnerability and risk to Covid-19.